Circular RNAs in hepatocellular carcinoma: biogenesis, function, and pathology - Rao, Guocheng; Peng, Xi; Tian, Yan; Fu, Xianghui; Zhang, Yuwei (Frontiers in Genetics, 2023)
Hepatocellular carcinoma (HCC) is one of the most common causes of cancer-related death worldwide. Both genetic and environmental factors through a multitude of underlying molecular mechanisms participate in the pathogenesis of HCC. Recently, numerous studies have shown that circular RNAs (circRNAs), an emerging class of non-coding RNAs characterized by the presence of covalent bonds linking 3′ and 5′ ends, play an important role in the initiation and progression of tumor, including HCC. In this review, we will outline the current status for the research of circRNAs, with emphasis on the various functions and mechanisms of circRNAs in HCC and its microenviroment. We also summarize and discuss recent advance of circRNAs as biomarkers and therapeutic targets. These efforts are anticipated to throw new insights into future perspectives about circRNAs in basic, translational and clinical research, eventually advancing the diagnosis, prevention and treatment of HCC.